Seroprevalence and Clinico-Epidemiological Correlates of Hepatitis B Infection in Pregnancy at a Booking Antenatal Clinic, Federal Medical Centre, Yenagoa - E. L., Kotingo; D.O.B., Allagoa; J. E., Omietimi; Eos, Aigere; P.W., Oweisi; C. T., John (European Scientific Journal, ESJ, 2018)
Background: Hepatitis B virus infection is considered a major worldwide public health problem. While adults that acquire acute infection usually recover, the chronic type is ultimately fatal both to them and their foetuses. In endemic areas, individuals are infected by vertical transmission or infection in early childhood. The seroprevalence rates of Hepatitis B in pregnancy vary according to the endemicity of a given area with very high prevalence rates mostly reported among developing nations in Asia and Africa. Objective: To determine the seroprevalence of hepatitis B surface antigen in pregnant women attending the antenatal clinic, identify the clinical and epidemiological correlates for hepatitis B in pregnancy and to make evidence based recommendations on screening protocols for our obstetric population at the Federal Medical Centre, Yenagoa. Methodology: This is a descriptive cross sectional study. Two hundred and twenty (220) consecutive healthy pregnant women attending the antenatal booking clinic of the hospital who met the inclusion criteria were recruited into this study after pretest counselling and obtaining consent from them. This was tested for HBsAg with commercially available in vitro diagnostic kits (one step test strips). Data was collected via a structured interviewer administered questionnaire. Data entry and analysis was done using SPSS (statistical package for social sciences) 22 statistical package (SPSS Inc., Illinois, U.S.A). P value less than 0.05 was European Scientific Journal February 2018 edition Vol.14, No.6 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431 280 taken as being significant. Results: The mean age of the pregnant women studied was 28.8 years ± 5.2 while the mean parity was 1.20 ± 1.16. 220 pregnant women who came for antenatal booking were recruited into this study. Of these, 4.6% (n=10) were seropositive for hepatitis B surface antigen (HBsAg). Multiple sexual partners and Female circumcision were the significant risk factors for HBsAg seropositivity (p<0.05). There was no significant association with respect to a history of jaundice or contact with a jaundiced patient, previous blood transfusion, intravenous drug abuse or sharing of sharps, previous surgery, episiotomies or dilatation and curettage (p>0.05). Conclusion: The intermediate endemicity of Hepatitis B virus infection in this study according to WHO classification, justifies the need for routine screening in pregnancy to identify and treat the infection accordingly as this will reduce the mother to child transmission. Multiple sexual partners and female circumcision are significant risk factors associated with Hepatitis B virus infection in this environment. Active and passive immunization to infants of HBsAg seropositive mothers is advocated.